The Effect of Leadership and Communication on Employee Performance at Maya Ubud Resort and Spa Gianyar-Bali - Putra Yasa, I Kadek; Subadra, I Nengah (Akademi Komunitas MAPINDO, 2023)
The purpose of this study is to determine the effect of leadership and communication on employee performance at Maya Ubud Resort and Spa Gianyar-Bali, partially and simultaneously. This study used stratified random sampling because it randomly selected 38 of the 269 employees of Maya Ubud Resort and Spa in each department. The data obtained was analysed with validity, reliability, classical assumption tests, correlation analysis, multiple linear regression analysis, and hypothesis testing (T and F tests), which were processed with SPSS 24 for Windows. The results of this study indicated that leadership partially had a positive and significant effect on employee performance at Maya Ubud Resort and Spa, with a t-count of 2.184, which was bigger than the t-table, which was 2.030, and a significance value of 0.036, which was smaller than 0.05. Second, communication partially had a positive and significant effect on employee performance at Maya Ubud Resort and Spa, with a t-count of 3.745, which was bigger than the t-table, which was 2.030, and a significance value of 0.001, which was smaller than 0.05. Leadership and communication simultaneously had a positive and significant effect on employee performance at Maya Ubud Resort and Spa. This was indicated by the f-count of leadership and communication being 10.090, which was bigger than the f-table, which was 3.260, and the significance value of 0.000, which was smaller than 0.05. The coefficient of determination showed that the contribution of leadership and communication to employee performance was 36.6%, while the remaining 63.4% was affected by other variables not examined in this study. Keywords: Leadership, Communication, Employee Performance